2012
DOI: 10.5761/atcs.ra.12.01926
|View full text |Cite
|
Sign up to set email alerts
|

The New Era of Staging as a Key for an Appropriate Treatment for Esophageal Cancer

Abstract: Fluorodeoxyglucose-positron emission tomography (FDG-PET) and computed tomography (CT) have become the gold standard for staging of esophageal cancer by detecting distant metastases, but metastatic lymph nodes are often difficult to diagnose from the size and standardized uptake value (SUV). If we compare the diagnostic performance of endoscopic ultrasonography (EUS), CT, and FDG-PET in staging of esophageal cancer, EUS is the most sensitive method to identify the detection of regional lymph node metastases, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…A previous study also investigated the correlation between girdin expression and clinical data using specimens resected from ESCC patients, and its immunohistochemical (IHC) data demonstrated a similar result, in that the overall survival was notably longer in samples with lower girdin expression compared with that in samples with a higher girdin expression (12). Esophageal cancer commonly occurs with highly invasive and metastatic characteristics (15,16) and due to the evidence demonstrating that girdin is involved in the regulation of cell motility (17,18), it was further investigated whether girdin had a role in the migratory behavior in ESSC ECA109 cells. The present study identified that talen-mediated girdin KO significantly inhibited cell migration in ECA109 cells, which is consistent with the findings from a study by Shibata et al (12), where cell migration was significantly reduced in ESCC KYSE cells transfected with girdin-specific small interfering RNA.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also investigated the correlation between girdin expression and clinical data using specimens resected from ESCC patients, and its immunohistochemical (IHC) data demonstrated a similar result, in that the overall survival was notably longer in samples with lower girdin expression compared with that in samples with a higher girdin expression (12). Esophageal cancer commonly occurs with highly invasive and metastatic characteristics (15,16) and due to the evidence demonstrating that girdin is involved in the regulation of cell motility (17,18), it was further investigated whether girdin had a role in the migratory behavior in ESSC ECA109 cells. The present study identified that talen-mediated girdin KO significantly inhibited cell migration in ECA109 cells, which is consistent with the findings from a study by Shibata et al (12), where cell migration was significantly reduced in ESCC KYSE cells transfected with girdin-specific small interfering RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest that N+ disease by more than one modality may confer a worse prognosis than patients with N+ disease by only one modality. While studies have looked to determine differences in sensitivity, specificity, and accuracy of each modality, perhaps CT, PET, and EUS evaluate separate characteristics of lymph nodes that work in synergy to differentiate N+ from N− . Although we did not find a statistically significant difference among the different combinations of positive studies, again, the number of patients in this study may limit the ability to detect subtle differences.…”
Section: Discussionmentioning
confidence: 58%
“…Because nodal status is a key determinant of treatment and prognosis, understanding the best combination and sequence of studies for accurate clinical staging is critical for these patients. While all three modalities are widely used, there is a lack of consensus regarding their use alone, in combination, or in sequence . Several studies have attempted to define the sensitivity, specificity, and accuracy of these tests, but no studies have evaluated the prognostic significance of concordance of two or more modalities …”
Section: Introductionmentioning
confidence: 99%
“…However, diagnosing lymph node metastasis is often difficult from its size and maximum standardized uptake value (SUVmax)[1]. The predictive value of PET/CT in primary staging in patients with esophageal carcinoma is under discussion.…”
mentioning
confidence: 99%